Proterozoic–Cambrian history of Dronning Maud Land in the context of Gondwana assembly - Bauer, Wilfried; Thomas, Robert J; Jacobs, Joachim (Proterozoic East Gondwana: Supercontinent Assembly and Breakup, 2003)
Dronning Maud Land contains a fragment of an Archaean craton covered by sedimentary and magmatic rocks of Mesoproterozoic age, surrounded by a Late Mesoproterozoic metamorphic belt. Tectonothermal events at the end of the Mesoproterozoic and in Late Neoproterozoic–Cambrian times (Pan-African) have been proved within the metamorphic belt. In western Dronning Maud Land a juvenile Mesoproterozoic basement was accreted to the craton at c. 1.1 Ga. Mesoproterozoic rocks were also detected by zircon SHRIMP dating of gneisses in central Dronning Maud Land, followed by a long hiatus for which geochronological data are lacking, an amphibolite to granulite facies metamorphism and syntectonic granitoid emplacement of Pan-African age have been dated. During this orogeny older structures were completely overprinted in a sinistral tranpressive deformation regime, leading to the mainly coast-parallel tectonic structures of the East Antarctic Orogen. Putting Antarctica back in its Gondwana position, the East Antarctic Orogen continues northward in East Africa as the East African Orogen, whereas a connection to the marginal Ross Orogen at the Pacific margin of East Antarctica is suggested along the Shackleton Range. The East Antarctic-East African Orogen resulted from closure of the Mozambique Ocean and collision of West and East Gondwana, i.e. western Dronning Maud Land was part of West Gondwana. During this collision the lithospheric mantle probably delaminated, allowing the asthenosphere to underplate the continental crust and producing heat for the voluminous, typically anhydrous, Pan-African granitoids of central Dronning Maud Land.
Keywords: Dronning Maud Land; geologi

Geological map of Heimefrontfjella, Dronning Maud Land, Antarctica (Scale 1:250,000) - Jacobs, Joachim; Bauer, Wilfried; Kreutzer, Stefan; Patzelt, Gernot; Schmidt, Rainer; Schulze, Peter; Siegesmund, Siegfried; Spaeth, Gerhard; Thomas, Robert J; Weber, Klaus; Zarske, Gerd (PANGAEA, 2009)
The geological overview map was compiled from 15 geological maps (1 : 25,000) and is based on Jacobs et al. 1996. The topographic basemaps were adapted from unpublished 1:250,000 provisional topographic maps, Institut f. Angewandte Geodäsie, Frankfurt, 1983. Part of the contour lines are from Radarsat (Liu et al. 2001).
Keywords: Dronning Maud Land; geologi; kart; topografi